Penemuan Hukum terhadap Kekosongan Norma Informed Consent Pasien Anak dalam Praktik Pelayanan Kesehatan di Indonesia - Muhammad Rifani; Lusiana Pratiwi Sukmajaya; Bianda Adeti Patriajaya; Anindya Putri Permatasari; Esa Susanthy Meirianna; Asep Sapsudin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze legal discovery regarding the normative void (vacuum of norm) of informed consent for pediatric patients within healthcare service practices in Indonesia. Normative legal research is employed, focusing on positive legal norms, legal principles, and evolving legal doctrines in health law. The research utilizes a statute approach and a conceptual approach. Based on the normative and conceptual analysis, it is concluded that Indonesian positive law still contains voids and ambiguities regarding informed consent for pediatric patients. The lack of synchronization between health law, child protection law, and civil law results in legal uncertainty in healthcare practices, particularly in determining the capacity of children to provide medical consent.